Influence of Intuition and Capability on Accelerated Product Development in Big-Medium Scaled Food Companies in Indonesia - Kurnia, Pepey Riawati (UI Scholars Hub, 2021)
To face the pressure of competition, more and more companies perform accelerated product development by shortening the product development time so that the product will arrive at the market at the shortest time. Food industry has also performed accelerated product development. Using evolution theory, contingency theory, market-based view, and resource-based view a research model has been built. Results of the research’s initial identification show that food industry in Indonesia is in growth level towards maturity level. Meanwhile, competition in the food industry is in moderate level towards hypercompetition level. Tactics of accelerated product development often carried out is by simplifying the product development steps to eliminating the product development steps. The innovation type used is incremental innovation since it is fast and easy. Results of the research give information that intuition and capabilities are the main motivating factors for big-medium scaled food companies in Indonesia to accelerate product development.